QUALITY CHARACTERISTICS OF COCONUT WATER AND ITS EFFECT ON HUMAN SUBJECTS - Ekoua Regina KRABI; Koffi Maïzan Jean-Paul BOUATENIN; Yabo Majoie Géroxie TOHOYESSOU; Lydia Karell KOKOLA; Semassa Josiane ADJOBIGNON; Wahauwouélé Hermann COULIBALY; Fatoumata CAMARA; Marina KOUSSEMON; Sébastien NIAMKÉ (Food and Environment Safety)
Coconut water, the clear liquid extracted from coconuts (Cocos nucifera L.), is a refreshing tropical drink with a booming market. However, despite its success, the moisturizing properties of this product remain controversial. This research aims to inform consumers about the hydrating power of coconut water sold on the streets of Abidjan. To achieve this objective, analyses were performed at several levels. Firstly, a survey of coconut water consumption was carried out, followed by in vitro experiments using biochemical, physicochemical, and functional analyses. The questionnaire survey revealed that coconut water was well known to consumers (100%) and that it was consumed mainly by people aged between 20 and 30 (47.5%) and between 15 and 20 (20.80%), for its fortifying (33.33%), digestive (29.33%), and refreshing (28.34%) properties. Coconut water contained carbohydrates (4.5±0.0%), dry matter (5.2±0.0070%), energy (19.92±0.0%), and ash (0.44±0.0 %). The coconut water beverage contained sodium at a concentration of 220.45±0.4949 mg, potassium (1591.02±6.10 mg), and phosphorus (276.1±10.18 mg). The last part of the analysis was essentially conducted in vivo by determining the volume of urine after the subjects had consumed the coconut water and mineral water. Generally speaking, the volume of urine after consumption of coconut water was lower than that after consumption of mineral water, with values falling from 138.5 mL (T1) to 66.67 mL (T4) and then from 41.67 mL (T1) to 36.33 mL (T4) for coconut water. It is the presence of potassium in coconut water that explains its effectiveness in promoting water retention. Coconut water is a diuretic and therefore cleanses the bladder. It is clear that coconut water seems to have a greater hydrating power than mineral water.